2015
DOI: 10.1080/21513732.2015.1031179
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of livestock grazing on plant species composition in montane forests on the northern slope of Mount Kilimanjaro, Tanzania

Abstract: The montane forests on Mount Kilimanjaro are part of the ecologically protected area and provide ecosystem services to the local communities on the lower slopes. Despite their ecological value, the montane forests on the northern slope of Mount Kilimanjaro have been affected by increased livestock grazing pressure due to prolonged drought and expansion of agricultural land. We examined the impacts of livestock grazing on plant species composition in the montane forests on the northern slope of Mount Kilimanjar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…The rainfall also varies with exposure to the wind blowing from the Indian Ocean where the northern slopes on the shadow sides receive much less rainfall [19]. The montane forest experiences two distinct rainy seasons where the long rainy period occurs between March and May and the short rain periods occurs between November and December and hence the rainfall pattern being bimodal [5]. The maximum mean annual rainfall reaches up to 3000 mm at 2100 m.a.s.l.…”
Section: Location and Characteristics Of The Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…The rainfall also varies with exposure to the wind blowing from the Indian Ocean where the northern slopes on the shadow sides receive much less rainfall [19]. The montane forest experiences two distinct rainy seasons where the long rainy period occurs between March and May and the short rain periods occurs between November and December and hence the rainfall pattern being bimodal [5]. The maximum mean annual rainfall reaches up to 3000 mm at 2100 m.a.s.l.…”
Section: Location and Characteristics Of The Study Areamentioning
confidence: 99%
“…Observation from this study demonstrated a significantly decreased in SOC with increased grazing pressure in the montane forest of Mount Kilimanjaro. Previously Kikoti and Mligo, (2015) [5] reported on the impact of livestock grazing on plant species composition and diversity including the natural regeneration patterns within the montane forest. These impacts are accompanied with changes in accumulation of soil organic carbon in the montane forest.…”
Section: The Effect Of Livestock Grazing On Soil Organic Carbon (Soc)mentioning
confidence: 99%
See 3 more Smart Citations